Critical Factors Influencing Facility Maintenance Management of Tertiary Institutional Buildings in Southwest Nigeria - Akinsola, O. E.; Hussaini, P. O.; Oyenuga, S.O.; Fatokun, A.O. (Mediterranean Journal of Social Sciences, 2012)
Building maintenance has until recently been a neglected field of technology in most of our governmental policy formulation and execution. This is reflected in the maintenance of housing stocks held in our various institution of Higher learning. Every Tertiary institutional building whether old or new requires being maintained and constitutes parts of our most valuable asset, providing learners with shelter facility for study, work and leisure. This project take as a look at the â€œAssessment of the Factors Influencing Maintenance Programme of Tertiary Institutional Buildings in Southwest Nigeriaâ€ through examination of environmental and climatic conditions, availability of funds, socio-political reasons, mishandling and overpopulation. Two hundred and fifty administered to were returned out of the Three hundred and fifty administered to Hostel occupants, Technical staffs and Maintenance organization heads. The method adopted was simple percentage and inferential statistical tool for the analysis of data. The findings of the study revealed that the claims of the Maintenance department to practicing combined maintenance of planned and unplanned are faulted. Findings revealed that they lacked the wherewithal to make it a success. This paper recommends that budget allocation for maintenance of tertiary institutional buildings be made by the government in view of the inflationary trend in the economy, adequate and skilful staff should be provided for the maintenance department to avoid delay in job execution, while rate of response to maintenance request, repair to damages and faults identified should be made faster.